Augustinian Recollect Legacy to the Church in Negros Island - Romanillos, Emmanuel Luis A. (Philippine Social Science Journal, 2020)
The Recollects’ arrival in 1848 impacted every aspect of life in Negros. Their enthusiasm, supported by affluent immigrants, contributed decisively to a climate of optimism and progress, placing Negros at the forefront of colonial provinces. Their evangelization effort converted countless unbelievers, settled later in new parishes. The Christian heritage of faith is deeply etched in Negrenses and settlers. The building legacy of Mauricio Ferrero, Manuel Gómara, Felipe Lerena—the cathedrals of Bacolod, San Carlos, Kabankalan—lives on. The pastoral work of Gregorio Espiga, Fernando Cuenca, Mariano Bernad is indelible in the annals of history. The educational apostolate in Bacolod, San Carlos, Valencia, Bayawan is reflected in their alumni in public service, business, and religious or priestly ministry. Forever we cherish the sojourn of Saint Ezekiel Moreno, Blessed Martín de San Nicolás, and Blessed José Rada, who touched the lives of our forefathers in Talisay, Binalbagan, and La Carlota.